Leveraging Artificial Intelligence Technologies in the Service of the Holy Quran and Its Sciences - Basheer Adnan (Asosiasi Khazanah Cendekia, 2024)
The research addresses the growing role of artificial intelligence in serving the Holy Quran and its sciences, reviewing the enormous potential that this field provides in improving the understanding, teaching, and learning of the Holy Quran. The research also aimed to demonstrate the importance of employing artificial intelligence technologies in serving the Holy Quran and its sciences, by presenting the importance of artificial intelligence technology and investing it in Islamic sciences, Islamic applications, serving the Noble Prophetic Hadith and its sciences, serving the objective interpretation of the Holy Quran, memorizing the Holy Quran and reciting it, in addition to issuing fatwas and spreading religious awareness. The research relied on a mixed research methodology, which included a qualitative analysis of the data, and the theoretical framework was prepared by referring to the literature that addressed the topic, including academic studies, websites, and electronic applications. By reviewing the applications of artificial intelligence and its importance to the topic under study, the results of the study showed great potential for using artificial intelligence in serving the Holy Quran and its sciences. These technologies are capable of facilitating the process of learning and teaching the Holy Quran and improving the understanding of meanings and interpretations .Based on these results, the study recommends intensifying research efforts in this field with a focus on areas such as analyzing Quranic narratives and understanding rhetorical meanings, encouraging cooperation between religious scholars and artificial intelligence experts to develop integrated applications that meet the needs of students and researchers, as well as encouraging religious and educational institutions to adopt these technologies and provide the necessary support for their development and application.